IMPLEMENTATION OF E-LKPD VIRUS MATERIAL BASED ON KNOW-LEARNED (K-L) STRATEGY TO TRAIN STUDENT METACOGNITIVE SKILLS - Rahmadani, Desi Lia Nur; Susantini, Endang (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2021)
Covid19 pandemic that emerged in 2020 caused learning to be carried out online, including in learning virus material. Virus material has abstract characteristics so it is difficult for students, proven by the average national exam in 2019, the result of virus material concept of 54.2 which is still below the minimum standard. Low learning outcomes can be overcome by metacognitive strategies. One type is Know-Learned. K-L that can be integrated into E-LKPD to help students achieve learning objectives. Based on these problems, research is needed on the application of E-LKPD using K-L metacognitive strategies on virus material during online learning. The research aims to describe the practicality and effectiveness of K-L E-LKPD using One-Group Pretest-Posttest Design. The research was conducted at SMAN 2 Mejayan on 26 students of X MIA 1 online. The results of the study the activities of students were 100% very practical category and the positive response of students was 92.1% belong to a very practical category. Learning outcomes based on the N-Gain score of 0.9 classified into a very high category, the completeness indicator items is 86.5% and the item sensitivity is 0.7. The results of the students' metacognitive skills were 3.375 very good categories based on four indicators namely: ability to determine initial and final knowledge; determine the level of confidence; comparing initial and final knowledge; and determine the score. These results conclude that the application of K-L E-LKPD on virus material is practical and effective in training students' metacognitive skills. Keywords: E-LKPD, virus, metacognitive Know-Learned, online learning